2012
DOI: 10.1159/000341598
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of UV Absorbance for Estimation of Phosphate Elimination during Hemodiafiltration

Abstract: Background: Phosphate is an important factor in explaining the high progress of vascular calcification among dialysis patients. Today, phosphate concentration is measured in plasma on a regular basis. The aim of this study was to find out if it is possible to estimate total removed phosphate (TRp) in spent dialysate utilizing UV absorbance during hemodiafiltration. Methods: Eleven patients were monitored online with UV absorbance at 297 nm, three times during one week each (n = 33). Dialysate samples were take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Optical monitoring of hemodialysis has been considered as a beneficial and cost-effective alternative to traditional methods to assess the effectiveness of the dialysis procedure without the need of frequent blood sampling [ 20 ]. The optical monitoring possibility of the phosphate removal during dialysis has been suggested by Enberg et al [ 15 ]. This study included 11 patients and 33 dialysis sessions, while absorbance at a single wavelength was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical monitoring of hemodialysis has been considered as a beneficial and cost-effective alternative to traditional methods to assess the effectiveness of the dialysis procedure without the need of frequent blood sampling [ 20 ]. The optical monitoring possibility of the phosphate removal during dialysis has been suggested by Enberg et al [ 15 ]. This study included 11 patients and 33 dialysis sessions, while absorbance at a single wavelength was used.…”
Section: Discussionmentioning
confidence: 99%
“…Methods for optical estimation of dialysis quality [ 10 ] and small [ 11 , 12 ], protein bound [ 13 ] and middle [ 14 ] molecular weight uremic retention solutes removal during dialysis has been proposed. Possibility for optical determination of phosphate elimination during dialysis has been also demonstrated [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the determination of UV-absorbance (A) in the spent dialysate/ultrafiltrate, described earlier [9][10][11] , a double-beam spectrophotometer (V-570, UV/VIS/NIR spectrophotometer and software version 1.53.01 for Windows, JASCO Corp., Japan) with an accuracy of ±0.3% was used. Scanning at the UV-range 190-400 nm was performed after each session using pure dialysate as reference.…”
Section: Uv-absorbance Scanningmentioning
confidence: 99%
“…Our group has previously shown possibilities to estimate the removal of small water soluble waste solutes during HD, utilizing UV-absorbance within a wavelength range of 280-297 nm [8][9][10] . Since urea certainly is not a representative for all removed solutes, and is known to be rather non-toxic, an optical monitoring technique that is suitable for middle molecule removal could be a valuable complement to urea-based dialysis dose parameters.…”
Section: Introductionmentioning
confidence: 99%
“…While ultraviolet (UV) absorbance monitoring of the spent dialysate [4][5][6] enables determining urea-based dialysis quality parameters [7,8], the potential of optical dialysis monitoring is wider. Earlier Toxins 2021, 13, 255 2 of 15 research has shown the potential of optical monitoring of the spent dialysate to estimate the removal of low molecular weight uremic toxins [9][10][11][12][13][14], elimination of electrolytes, such as phosphate and calcium, [15,16], and possibly for nutrition assessment [17]. As a result, the UV monitoring of the removal of low molecule weight uremic solutes by HD treatment has become commonly applied in the treatment practice worldwide [18][19][20].…”
Section: Introductionmentioning
confidence: 99%